The THE INFLUENCE OF NEGATIVE ELECTRONIC WORD OF MOUTH AND VARIETY SEEKING ON BRAND SWITCHING BEHAVIOR WITH CUSTOMER ENGANGEMENT AS AN INTERVENING VARIABLE (A STUDY ON SCARLETT SERUM PRODUCTS AMONG GEN Z) - Dertaida Panjaitan; Indrawati (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The growth of the cosmetics industry in Indonesia is influenced by the increasing demand for beauty products. One of the contributing factors to this trend is a common issue faced by women, especially Gen Z, which is dull skin. One of the most purchased beauty products by Gen Z is facial serum. The aim of this research is to examine the influence of Negative EWOM (Electronic Word of Mouth) and variety seeking on brand switching behavior, with customer engagement as an intervening variable for Scarlett facial serum among Gen Z consumers. This study employs a quantitative approach with descriptive and causal research methods. Data collection is done through a questionnaire survey with 300 respondents who use Scarlett facial serum in Indonesia. The data analysis technique used is Structural Equation Modeling (SEM) using SmartPLS for research data analysis. The research findings indicate that Negative EWOM have a positive influence on brand switching behavior, Negative EWOM have a negative influence on customer engagement, variety seeking have a negative influence on customer engagement, variety seeking have a positive influence on brand switching behavior, customer engagement have a negative influence on brand switching behavior, Variety seeking on brand switching behavior through customer engagement as an intervening variable have a positive influence, Negative E-WOM on brand switching behavior through customer engagement as an intervening variable also have a positive influence.This research has implications for companies, including the need for companies to enhance product quality and their brand image in response to Negative E-WOM. Companies should also continue to innovate by improving product quality and uniqueness. Additionally, understanding customer preferences and market trends is crucial for competing in a market with many similar products. Maintaining customer interactions can also keep the company top of mind among customers, preventing them from switching to other brands. These actions are necessary to retain customers and prevent brand switching. Referring to several previous studies, research on negative word of mouth, brand switching behavior, variety seeking, and customer engagement has never been conducted simultaneously with the same variables and object.